PENGUATAN PENDIDIKAN KARAKTER MELALUI KEGIATAN KOKURIKULER (MENGETIK FONT ARAB YH DAN MUROTAL AL-QURAN) DI MI TARBIYATUS SIBYAN GENTENG - Firma Yudha (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2019)
Community service aims to develop character education habituation through co-curricular activities in MI Tarbiyatus Sibyan Genteng-Banyuwangi. Habituation habits in the courricular activities are seven competencies that include; Competency of Faith and Takwa, science and technology competence, leadership competence, social and entrepreneurship competence, exercise and artistic competence, environmental competence, and communication competence. The result of this community devotion is the relationship of co-curricular activities with character education as a balance and harmony between the knowledge gained in class with the reinforcement of the character gained from the co-curricular activities. And able to instill the values of sublime ethics that become a culture in social life both at home, school, and society.